"A Study on Relation Between Attacks of Migraine Headache and Serum- Magnesium Level" - A Masoud (Tehran University of Medical Sciences, 2003)
Migraine is one of the common varieties of headache. It involves 4 to 6 percent of men and 13 to 16 percent of women under 30 years in more than 80% of cases. Some studies have shown that in 50% of patients serum magnesium level decreases during attacks of headache and using magnesium tablets and intravenous magnesium sulfate is more effective for treatment of migraine attack, than placebo. This is a cross sectional, analytical study on 50 patients referring to private neurology clinics and Shahid Beheshti Hospital of Kashan University of Medical Sciences (KAUMS). Serum magnesium level studied during the attack of headache and in remission in each of 50 patients. All predisposing factors such as age, sex, cigarette smoking, trauma and family history of migraine and so on were searched. Forty - five of 50 patients (90%) were female and 5 (10%) were male. Thirtyfour (68%) of cases were between 31 and 45 years old. In this age range 30 (60%) were female and 4 (8%) male. Seven (14%) had history of trauma. Five (10%) cigarette smoker, 44 (88%) had history of stress, and 30 (60%) had history of migraine in their family. Serum magnesium level was 2.1 in remission phase, and 1.7 during attack (P=0.001), although both are in normal range (N=1.6 - 2.7). Serum magnesium level decreases during the attacks of migraine headache, so using magnesium containing drugs may be useful in its control.